Fall into HIV diagnosis: case report - Coelho, Claudia (2024)
Introduction: The prevalence of human immunodeficiency virus (HIV) infection seems to be stabilized at 0.7% but in some countries, it continues to rise. For many years it was only associated with the African continent and specific populations, but today there is an increase in the incidence in developed countries. This infection can be asymptomatic or have non-specific symptoms. Those depend on the stage of the disease, the viral load, or the host’s immune status. This case shows how the diagnosis of HIV remains a real challenge, reporting a rare form of symptomatic presentation. Case description: A 21-year-old male, with Angolan nationality, went to primary health care consultation due to frequent falls in the last month associated with a sensation of lack of strength in the lower limbs. During physical evaluation, a discrete global reduction of strength in the four extremities was noted, most markedly in the left upper limb. The patient denied risky sexual practices or parenteral drug consumption. After carrying out complementary analytical studies, an electromyographic study, and computed tomography of the brain, cervical, and lumbar spine, the results came back positive for HIV infection as the cause of the presented symptoms. Comment: What at first seemed to be symptoms related to an incipient neuromuscular disease turned out to be the diagnosis of a viral infection. Due to the nonspecificity of the symptoms, it is important to maintain a high level of suspicion of HIV infection. In this case, peripheral neuropathy was the only manifestation reported. Although it has a prevalence of up to 60% among the infected, it is rare as an isolated sign. Its aetiopathology is still unclear, but it is known to be multifactorial and progressive. Nowadays the patient is stable after the initiation of antiretroviral therapy, with improvement in symptomology.